A quinoidal bis-phenalenyl-fused porphyrin with supramolecular organization and broad near-infrared absorption. Issue 9 (21st December 2015) - Diev, Vyacheslav V.; Femia, Denise; Zhong, Qiwen; Djurovich, Peter I.; Haiges, Ralf; Thompson, Mark E.
Abstract : A concise synthesis is disclosed for a quinoidal bis-phenalenyl-fused porphyrin that displays near-infrared absorption and supramolecular organization in the solid state. Abstract : A bis-phenalenyl-fused porphyrin has been synthesized by thermal dehydro-aromatization reaction regioselectively as a single syn -isomer. X-ray crystal structure revealed that both phenalenyl units of this porphyrin have close π–π contacts forming continuous network of interacting porphyrin rings. A broad and intense NIR absorption can be attributed to quinoidal character of bis-phenalenyl-fused porphyrin.